The Arts Of Metaphor And Its Depictions In The Holy Quran: Surat Al-Kahf As An Example - Mohamed Bin Haji Ibrahim; Yaakob Hasan; Yuslina Binti Mohamed (Usuli Faqih Research Centre PLT, 2024)
Indexed by MyCite